Beyond monetary value: how reward type drives cheating in a gender-judgment task - Chen, Guan-Zhao; Zhao, Fei-Fei; Li, Hao-Ming; Wu, Yu-Wei; Yan, Wen-Jing (Frontiers in Psychology, 2024)
Background Investigating the effects of monetary incentives on dishonest behavior provides valuable insights into human integrity and ethical decision-making processes. This study is conducted through the lens of self-concept maintenance theory. Aim The aim of this study is to examine the influence of different types of rewards (score-based vs. monetary) and their magnitude on dishonest behavior within a gender judgment task. Method Using a quantitative experimental design, this study involved 116 participants who were randomly assigned to conditions that differed in reward type (score or money) and magnitude (10 yuan vs. 50 yuan). Dishonest behavior was assessed using a gender judgment task with mechanisms to simulate conditions conducive to planned cheating. Results Results revealed significant differences in dishonesty rates between score and money conditions, with a higher proportion of dishonest participants observed in the score condition compared to the money condition. The timing of initial cheating was earlier in the score condition compared to the money condition. No significant differences were found in the proportion of dishonest participants, the cheating rate, or the timing of initial cheating across reward levels within either condition. The rate of cheating increased over time, suggesting a temporal dynamic in unethical decision making. Conclusion The study demonstrates that the nature of rewards significantly influences the likelihood of dishonest behavior, with intangible score-based rewards facilitating rationalizations for dishonesty more readily than tangible financial incentives. These findings enrich the understanding of moral psychology by highlighting the complex interplay between reward types, ethical rationalization, and the dynamics of dishonest behavior.